Assessing the impact of Instagram use and deliberate self‐harm in adolescents: A scoping review. (22nd August 2022) - Moss, Carla; Wibberley, Christopher; Witham, Gary
Abstract: The use of Instagram by adolescents to access deliberate self‐harm content is a growing concern among scholars, mental health professionals and families, with many adolescents (10–19‐year‐olds) imitating offline what they have seen online. This scoping review aims to investigate the extent to which Instagram use impacts the mental health of its adolescent users, identifying whether there is a relationship between time spent on Instagram and engagement in deliberate self‐harm. The databases, PubMed, Web of Science, Google scholar, APA PsycInfo, CINAHL and child development and adolescent studies were explored, and after applying the inclusion/exclusion criteria, 15 papers were included in this review. Thematic analysis indicated that there was a relationship between time spent on Instagram and deliberate self‐harm; desensitization of deliberate self‐harm resulting in normalization; social contagion and that Instagram provided a sense of belonging to its users who engaged in deliberate self‐harm. Implications of this research is that it is quickly outdated as new social media platforms are developed and that the reliance on self‐reports does not have high validity or reliability.